A deep insight into the intrinsic healing mechanism in ureido‐pyrimidinone copolymers. (30th July 2018) - Suriano, Raffaella; Brambilla, Luigi; Tommasini, Matteo; Turri, Stefano
Abstract : Self‐repairing polymers are gaining ever‐increasing attention and are becoming very appealing for future sustainable societies because they can enhance the durability of materials. A route to develop intrinsically self‐repairing materials is the design of self‐assembling supramolecular polymers, such as those bearing self‐complementary hydrogen bonding 2‐ureido‐4[1H]‐pyrimidinone (UPy) motifs. A deeper understanding of the self‐assembly dynamics of UPy groups in supramolecular polymers is essential for controlling and exploiting their self‐healing behavior. Here, two model copolymers with different molecular weights, made of butyl acrylate (BA) and a methacrylate comonomer bearing UPy groups, are synthesized. The copolymer molecular weight has an effect on glass transition temperatures, thermo‐mechanical properties, and self‐healing abilities. A lower polymer molecular weight increases chain mobility and decreases the glass transition temperature, thus improving self‐repairing capabilities. Fourier‐transform Infrared (FT‐IR) spectroscopy analysis performed on UPy‐BA copolymers with a more efficient self‐healing behavior indicates the presence of specific markers for the formation of UPy‐UPy dimers and for the breakage of multiple hydrogen bonds between UPy units. The results first demonstrate the possibility to monitor the supramolecular UPy assembly by vibrational spectroscopy during heat‐triggered healing. This study enables self‐healing properties of UPy‐based copolymers at the macroscopic scale to be directly linked with the formation of UPy‐UPy dimers acting as physical cross‐links at the nanoscale.